THE EFFECT OF IMPLEMENTING THE STEAM APPROACH THROUGH ENVIRONMENTAL POLLUTION EXPERIMENTS ON CRITICAL THINKING SKILLS AND CREATIVITY OF EARLY CHILDHOOD - Erine Agustia; Muci Herliyanto; Sahara Wita (BioCONCETTA, 2026)
Abstract: Research on early childhood education at Natuna International Kindergarten reveals challenges in fostering critical thinking and environmental awareness due to traditional teacher-centered learning approaches and reliance on commercial worksheets. To address these issues, the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach integrated with environmental pollution experiments was implemented using a quasi-experimental design (Randomized Control Group Posttest Only Design with a 2x2 Factorial structure). The research population comprised students at Natuna International Kindergarten during the 2025/2026 academic year, with Group D selected as the experimental class (STEAM-based environmental pollution experiments) and Group C as the control class (conventional learning). Data were gathered through observation checklists and performance assessment rubrics evaluating critical thinking, cognitive problem-solving, and creative output. The findings demonstrated that children taught via the STEAM environmental pollution experiment approach achieved significantly higher learning competencies across cognitive, creative, and manipulative-psychomotor domains compared to those taught with traditional methods. Furthermore, STEAM effectively bridged theoretical environmental awareness with hands-on exploration across varying initial ability levels without significant interaction effects, proving to be an impactful framework for early childhood development in border region educational institutions.